Risk of tuberculosis transmission by children in Hamburg, Germany. (April 2023) - Diel, Roland; Meywald-Walter, Karen; Schwarzbach, Christian; Voss, Klaas; Dreyer, Viola; Niemann, Stefan
Abstract: Background: Data from a prospective molecular-epidemiologic study (1997–2021) in Hamburg, Germany, were evaluated to assess the transmission risk of Mycobacterium tuberculosis complex (Mtbc) by children <15 years in a low-incidence setting. Methods: Isolates of Mtbc were genotyped whole genome sequencing, applying a core genome multilocus sequence typing scheme. Close contacts of culture-confirmed children were examined for latent Mtbc infections (LTBI) with particular focus on IGRA testing. Results: Out of 3154 culture-confirmed tuberculosis (TB) cases, 79 (2.5%) were children <15 years. Of those, 52 (58%) had pulmonary TB. Genotyping revealed that 35 of the 52 children (67%) were epidemiologically confirmed secondary cluster members; all of their source cases were adults. Six immigrant children presented without a presumed source case; their TB diagnoses came on average 48 weeks (interquartile range [IQR] 71) after their arrival in Germany. Three German-born children were determined to have been infected by adult relatives while visiting their parents' home country. Of the 317 children's close contacts tested with QuantiFERON-TB Gold-In Tube for LTBI, only 21 (6.6%) were positive. Absent a history of prior exposure or immigration from a high-incidence country, none of the contacts of younger (<10 years) TB-afflicted children was latently infected, whereas 2 older children infected 12 of their contacts, children and adults. During a mean observational period of 551 weeks (IQR 735) on average, no secondary TB cases appeared. Conclusions: Children with pulmonary TB disease, especially those aged below 10 years, rarely transmit Mtbc to their close contacts in a low-incidence setting. Highlights: The role of children <15 years in transmitting Mycobacterium tuberculosis (Mtbc) as verified by genotyping remains unclear. Transmission links of Mtbc were prospectively observed by whole genome sequencing (WGS) in Hamburg, Germany, since 1997. Transmissions by 52 children with culture-confirmed pulmonary tuberculosis (TB) were searched over a mean period of 551 weeks. Children with pulmonary TB disease, especially those aged below 10 years, rarely transmit Mtbc in a low-incidence setting.